Methodology for the Development of National Digital Cadastral Database - A. Kadir, Abd. Majid (2003)
Coordinated Cadastral System (CCS) – a cadastral reform programme to improve the cadastral survey system. Implementation of CCS – feasible, according to results of feasibility study.